A Lei Geral de Proteção de Dados: uma análise comparada ao novo modelo chinês - Law, Thomas (2020)
This doctoral thesis aims to answer the following question: in the context of entrepreneurial activity, how does data protection regulation guided by Chinese policy approach the current Brazilian General Data Protection Law (Law No. 13,709, of 14 August 2018, as amended by Law No. 13.853, of July 8, 2019)? The research was carried out through the analysis of the concept of privacy, data capitalism, Big Data, blockchain and industry 4.0. In addition, we carry out an analysis of China's economic progress and Artificial Intelligence, as well as Brazil and China relations in a global and technological economic scenario, since the work is directly linked to the flow of information and the dynamic relationships of the virtual market contemporary. In addition, we address the Cyber Security Act of the People's Republic of China in force since June 2017 and the data protection policies of that Asian country. In the last chapter, an approach was made to the historical evolution of data protection, the General Data Protection Regulation (GDPR) in Europe and the General Data Protection Law (LGPD) in Brazil. We emphasize the importance of the General Data Protection Law, even though it is in the vacatio legis period, this legal instrument places Brazil on a level of international credibility, since data protection is essential for all citizens, especially in this century, where we live. It also urges that, according to Provisional Measure no. 959/2020, of April 29, 2020; Article 4 extended the aforementioned vacatio legis of the LGPD to May 3, 2021. In addition, it extends to August 1, 2021 the validity of the articles that establish penalties for companies that breach the provisions of the law. Finally, a comparative analysis between data protection in Brazil and China, answering in an affirmative way the question proposed in the present work, through self-regulation, that is, that Brazilian and multinational companies operating in Brazil adopt a compliance model and data protection accountability